KEBIJAKAN PEMERINTAH DALAM PENGENDALIAN COVID-19 DI PROVINSI NUSA TENGGARA BARAT - Abdul Rahman; Lalu Satria Utama (Institut Pemerintahan Dalam Negeri, 2020)
The COVID-19 pandemic has forced this nation to change attitudes and see things in different ways. All sectors in the country are not able to produce optimally, both the service sector and the field sector. However, the safety of the entire citizenry must be pursued even in difficult times. The role of academics in helping the government fight the COVID-19 pandemic is to share their thoughts in the fight against the pandemic. One of the things that can be done is to help the government disseminate Regulations Regional West Nusa Tenggara Province Number 7 the Year 2020 About the Infectious Diseases Control and provide thoughts on anticipatory and preventive measures for COVID-19.